Associations of diabetes mellitus with site-specific cancer mortality in the Asia-Pacific region - Lam, E.; Batty, G.; Huxley, Rachel; Martiniuk, A.; Barzi, F.; Lam, T.; Lawes, C.; Giles, G.; Welborn, T.; Ueshima, H.; Tamakoshi, A.; Woo, J.; et al. (2011)
Background: Owing to the increasing prevalence of obesity and diabetes in Asia, and the paucity of studies, we examined the influence of raised blood glucose and diabetes on cancer mortality risk. Materials and methods: Thirty-six cohort Asian and Australasian studies provided 367 361 participants (74% from Asia); 6% had diabetes at baseline. Associations between diabetes and site-specific cancer mortality were estimated using time-dependent Cox models, stratified by study and sex, and adjusted for age. Results: During a median follow-up of 4.0 years, there were 5992 deaths due to cancer (74% Asian; 41% female). Participants with diabetes had 23% greater risk of mortality from all-cause cancer compared with those without: hazard ratio (HR) 1.23 [95% confidence interval (CI) 1.12, 1.35]. Diabetes was associated with mortality due to cancer of the liver (HR 1.51; 95% CI 1.19, 1.91), pancreas (HR 1.78; 95% CI 1.20, 2.65), and, less strongly, colorectum (HR 1.32; 95% CI 0.98, 1.78). There was no evidence of sex- or region-specific differences in these associations. The population attributable fractions for cancer mortality due to diabetes were generally higher for Asia compared with non-Asian populations. Conclusion: Diabetes is associated with increased mortality from selected cancers in Asian and non-Asian populations. © The Author 2010. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved.